1994
DOI: 10.1016/0735-1097(94)90647-5
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced intravascular ultrasound: Validation of a new technique for delineation of the vessel wall boundary

Abstract: This preliminary study shows that delineation of the vessel wall boundary using echogenic contrast agents during intravascular ultrasound is safe and feasible. Because of higher contrast intensity and homogeneity, SHU 454 and SHU 508 are superior to other agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Hausmann et al reported that in performing IVUS on a dog coronary artery, the intracoronary administration of an echogenic contrast agent improved the the border's detectability in the coronary artery lumen. 21 Takaiwa et al also reported that when assessing coronary artery lesions before and after intervention, the administration of an echogenic contrast agent with IVUS was useful. 22 In the present study, the border between the in-stent neointima and the vessel lumen in the IVUS images was delineated vividly for all 24 subjects after the intracoronary infusion of an echogenic contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…Hausmann et al reported that in performing IVUS on a dog coronary artery, the intracoronary administration of an echogenic contrast agent improved the the border's detectability in the coronary artery lumen. 21 Takaiwa et al also reported that when assessing coronary artery lesions before and after intervention, the administration of an echogenic contrast agent with IVUS was useful. 22 In the present study, the border between the in-stent neointima and the vessel lumen in the IVUS images was delineated vividly for all 24 subjects after the intracoronary infusion of an echogenic contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…Some experiments have shown the feasibility and safety of contrastenhanced ICUS [9,10], but to our knowledge this is the first report of the suitable contrast agents for ICUS in humans.…”
Section: Discussionmentioning
confidence: 96%
“…Delineation percentage was determined as the percentage of the patients with arterial circumference visualized clearly after injection of each contrast agent within all the patients. To evaluate the homogeneity of luminal contrast, the optimal end-systolic frame was selected and qualitative grading was performed according to Hausmann et al [10]: 0 ϭ no bubbles; 1 ϭ individual microbubbles discernible; 2 ϭ a mixture of individual microbubbles and homogeneous opacification; 3 ϭ completely homogeneous throughout. We evaluated coronary homogeneity and false lumen homogeneity using this scoring system.…”
Section: Analysis Of Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 An echogenic contrast agent like sonicated ioxaglate is safe and effective for myocardial contrast echocardiography. 2 Although contrast agents may detect a dissection plane or an ulcerated plaque that is connected to the lumen, 1 subtle morphologic changes of the luminal surface may be missed due to backscatter from blood cells. To overcome these technical difficulties, we injected 5% glucose solution into the coronary artery during IVUS imaging to provide a negative contrast agent that avoids backscatter from red blood cells.…”
mentioning
confidence: 99%